Sale of Goods Act: a comparative study between Malaysia and United Kingdom (UK) on the issue of implied terms / Aziana Anura Khairul Anuar, Nik Nazriani Nik Ab. Rahman and Nurun Najwa Zawawi. - Khairul Anuar, Aziana Anura; Nik Ab. Rahman, Nik Nazriani; Zawawi, Nurun Najwa (Faculty of Law, 2011)
This research project is about a comparative study on the issue of implied terms and conditions between Malaysia and United Kingdom in furtherance of the sale of goods. The latter act of United Kingdom Sale of Goods Act 1979 has itself been amended on several occasions and furthermore, added protection to the existing statutes and favours more on consumers. Therefore, the purpose of this project research is to identify the weaknesses in the Malaysian Sale of Goods Act 1957 relating to implied terms and conditions as to strengthen the buyer's right as well as to sustain with the development and provides greater protection to the buyers. In addition, this research project is trying to find a way to improve on the effect of exclusion clause which overruled the implied term provision that may abolish on the protection given to the consumers thus gives total exclusion on the liability of the sellers. This research will examine on the provisions of both statutes, that is, the Malaysian Sale of Goods Act 1957 and the United Kingdom Sale of Goods Act 1979 relating to implied terms and exclusion clause.